Effect of Somatostatin Analogue (SMS 201-995) Administration on Portal Blood Flow in Patients with Liver Cirrhosis - S. KAPICIOĞLU; O. YEŞİLDAĞ and E. OVALI and A.H. BAKİ and N. KAYA (Turkish Journal of Gastroenterology, 2020)
-